Inventarisasi Jenis-Jenis Anggrek di Kawasan Banyak Angkrem dan Kedung Kopong, Kecamatan Salaman, Kabupaten Magelang, Jawa Tengah - Bela Prapitasari; Bintang Jalu Rais Al Amin; Taufiq Rezaldi; Alviana Nur Ahliyani; Masfufah Lutvita Kenza; Tazkia Aulia Nafiah (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
Banyak Angkrem and Kedung Kopong are medium lowland tropical rain forest areas where many types of orchids can be found. This study aims to determine the types and diversity of orchids found in the area of ​​Banyak Angkrem and Kedung Kopong. Data was collected using the Visual Encounter Survey (VES) method with a radius to the right and to the left 5 m from the observation path with a research area ​​6.24 ha. The results showed that in the two areas found 15 species of orchids consisting of 10 species of epiphytic orchids (Acriopsis lilifolia, Agrostophyllum laxum, Bulbophyllum sp 1, Bulbophyllum sp 2, Dendrobium sagittatum, Dendrobium sp, Oberonia lotsyana, Pholidota sp, Polystaschya concreta, Vanila. planifolia) and 5 species of terrestrial orchids (Geodorum densivelorum, Malaxis ophrydis, Malaxis sp, Nervilia plicata, Perystilus goodyroides). The level of diversity (H ') of orchids in the two regions is classified as moderate with an H' value of 2.22